Finite element analysis of pressure distribution in taper locks - Lee, Nicholas Zheng Ting (Nanyang Technological University, 2022)
Taper lock bush, also referred to as a taper bush, is a shaft hub connector widely used in Power Transmission Drives for coupling of shaft onto hubs such as gears, pulleys and sprockets. The taper lock bush consists of a tapered outer surface that fits with a matching tapered hub and an inner cylindrical surface that fits with the shaft. As the use of taper lock bush for shaft hub connections becomes more widespread, it is imperative that analyses are conducted to understand the pressures developed on the contact interfaces. Therefore, this project studies the contact pressure distribution on taper lock bushes of varying taper angles. Numerical methods such as finite element method is a powerful tool in determining the pressure distribution on contact interfaces. This project uses the Finite Element Analysis (FEA) software, ANSYS Parametric Design Language (APDL) Student Version to obtain the contact pressure distribution over the taper lock bush. First, a two-dimensional axisymmetric analysis is carried out on the taper lock assembly. The results show a high contact pressure at the larger end of the bush and decreases to a lower pressure at the smaller end of the bush. Contact pressures are generally uniformly distributed at the middle section of the bush. It is also noted that as taper angle increases, contact pressure experienced by the bush also increases. Next, a three-dimensional analysis is carried out. Two contact pressures distributions are analysed, one at the interface between the tapered surface of bush and pulley hub, and another at the interface between the shaft and inner core of taper lock bush. The results from the analysis showed that as taper angle increases contact pressure experienced by the taper lock bush and shaft also increases. Contact pressure experienced at the larger diameter of taper lock bush is higher compared to contact pressure at the smaller diameter of the bush. Along the axial direction, contact pressure is generally uniform for both the taper lock bush and shaft.